2012
DOI: 10.1097/brs.0b013e3182127457
|View full text |Cite
|
Sign up to set email alerts
|

The Access Randomized Clinical Trial of Public Versus Private Physiotherapy for Low Back Pain

Abstract: Despite differences between public and private PT regarding waiting times for treatment and therapist experience, there were no significant differences between groups in the majority of clinical outcome measure scores at follow-up, apart from SF-36 Role Physical and satisfaction with treatment outcome in favor of the private PT group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…Although also for Casserley-Feeney et al 29 EQ-5D and RMDQ presented similar results, this latter study evidenced that RMDQ is more sensitive than EQ-5D to small differences at low levels of disability. This lack of sensitivity to change in health states seems confirmed also by other studies.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Although also for Casserley-Feeney et al 29 EQ-5D and RMDQ presented similar results, this latter study evidenced that RMDQ is more sensitive than EQ-5D to small differences at low levels of disability. This lack of sensitivity to change in health states seems confirmed also by other studies.…”
Section: Resultssupporting
confidence: 77%
“… 25 , 28 , 29 , 31 , 33 , 36 , 41 Carr et al , 28 for instance, registered an increase in EQ-5D mean values from baseline to 3 months of 0.028 and from baseline to 12 months of 0.045 for the individual physiotherapy group, whereas improvements for the group exercise were milder. Similarly, Casserley-Feeney et al 29 reported EQ-5D to differ between public physiotherapy and private physiotherapy patients, Djas and Kalim 33 for the instrument to be sensitive to differences between patients undergoing radiography and patients not undergoing radiography and Wilkens et al 41 for the measurement to recognize patients administered with glucosamine and patients administered with placebo. Bastiaenen et al , 25 Hellum et al , 36 and Cox et al 31 reported similar results.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The EQ5D is a widely used health‐related quality of life (QoL) measure that contains five domains, namely, mobility, self‐care, usual activities, pain/discomfort, and anxiety/depression and includes a VAS for overall health . It has been shown to be applicable to, and valid for, a wide range of health conditions and treatments .…”
Section: Methodsmentioning
confidence: 99%
“…was measured in the patients with hip arthroplasty. Subjective outcome and satisfaction are known to be different constructs that are able to act independently of each other [22]. The low ceiling effect of both types of GSOS encourages their use in both clinical and research situations from this perspective.…”
Section: Utilitymentioning
confidence: 98%